2009
DOI: 10.1097/hcm.0b013e3181b3eade
|View full text |Cite
|
Sign up to set email alerts
|

Three Components of Organizational Commitment and Job Satisfaction of Hospital Nurses in Iran

Abstract: The 3 components of commitment are variously related to job satisfaction. Nursing managers should pay attention to different components of commitment variously to promote the appropriate type of commitment needed for specific situation in which they work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…It has been shown that organizational commitment has effects on positive job outcomes, including reduced absenteeism and turnover, and increased organizational citizenship behavior, efforts related to the job, job performance, as well as the organization's effectiveness in providing quality health services. [30] On the other hand, the observance of justice is the key to the organization and its employee's survival and development. [14] Therefore, this study aimed to review the effects of perceived organizational justice and its components on organizational commitment of administrative and financial employees of Shiraz University of Medical Sciences general hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that organizational commitment has effects on positive job outcomes, including reduced absenteeism and turnover, and increased organizational citizenship behavior, efforts related to the job, job performance, as well as the organization's effectiveness in providing quality health services. [30] On the other hand, the observance of justice is the key to the organization and its employee's survival and development. [14] Therefore, this study aimed to review the effects of perceived organizational justice and its components on organizational commitment of administrative and financial employees of Shiraz University of Medical Sciences general hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…(1993), and Meyer and Allen (1997) were used in 17 out of 33 included studies. [ 14 16 17 18 22 23 24 25 29 31 32 33 34 35 41 42 44 ] According to Meyer and Allen, OC contains the following three dimensions: (1) Affective commitment that refers to the members of an organization who are emotionally attached to, identify themselves with, and feel devoted to an organization; (2) continuance commitment that describes the employees who are committed because they believe the costs associated with leaving the organization are too high and, hence, they remain; and (3) normative commitment that refers to the group of employees who feel like they should stay with the organization beyond a sense of obligation. [ 47 ] It is noteworthy that 11 studies used the affective OC subscale of each of the above scales.…”
Section: R Esultsmentioning
confidence: 99%
“…The present study is an attempt to conceptualise the phenomenon of nurses’ job satisfaction among Iranian hospital‐based practicing nurses. The interrelationship and correlates of job satisfaction and its components among Iranian nurses have not been examined (Jahangir & Shokrpour 2009). This study extensively reviews the job satisfaction literature in order to highlight the dynamism in the conceptualisation of job satisfaction over time (Tovey & Adams 1999).…”
Section: Introductionmentioning
confidence: 99%